New data on the genus Trichohoplorana Breuning, 1961 (Coleoptera: Cerambycidae: Lamiinae) - Liang, Wen-Bo; Xie, Guang-Lin; Jiang, Guo-Fang (Zootaxa, 2026)
In this work, a new species of the genus Trichohoplorana Breuning, 1961 is described and illustrated, namely Trichohoplorana subtuberculata sp. nov. from Hunan and Guangdong provinces, China. Additionally, the first record and description of the female of Trichohoplorana juglandis Holzschuh, 1989 from Hubei province are provided.